Preparation of a Growth Hormone Receptor/Prolactin Receptor Bispecific Antibody Antagonist Which Exhibited Anti-Cancer Activity - Chen, Xin; Wu, Di; Zheng, Yan; Liu, Xingxing; Wang, Jianmeng (Frontiers in Pharmacology, 2020)
Studies show that prolactin receptor (PRLR) and growth hormone receptor (GHR) are closely related to the occurrence and development of some tumors (such as breast cancer), and breast cancer cell endogenously express GHR, PRLR and GHR-PRLR heterodimer. In this case, the combined use of PRLR or GHR inhibitors may produce better anti-breast cancer potential than PRLR or GHR inhibitors alone. This has led to develop the dual-function GHR/PRLR antagonists with anti-breast cancer potential. For this, we used hybridoma technology to generate an anti-idiotypic antibody (termed H53). We then used various techniques, including competitive ELISA, competitive receptor binding analysis, immunoelectron microscopy and indirect immunofluorescence assay to identify H53, and the results show that H53 behave as a typical internal image anti-idiotypic antibody (Ab2β). Further experiments indicate that H53 is a dual-function inhibitor, which not only inhibits PRLR-mediated intracellular signaling, but also inhibit GHR-mediated intracellular signaling in a dose-dependent manner. H53 inhibit PRL/GH-driven cancer cell proliferation. Our data indicates that H53 exhibits potential biological activity against breast tumors, which implies that internal image anti-idiotypic antibodies may offer a novel strategy for the development of PRLR/GHR dual-function antagonists for breast cancer therapy.